Woodward H. Brown letter to Nicholas S. Halmi regarding shorebirds and others seen after the Red Rock flood pool receded, May 25, 1973 - Brown, Woodward H.et al (1973)
Letter from Woodward H. Brown to Nicholas S. Halmi reporting on shorebirds seen after the Red Rock flood pool receded. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1973. Epson - sheet feed/flatbed